Advancing Monoclonal Antibody Manufacturing: Process Optimization, Cost Reduction Strategies, and Emerging Technologies - Ranbhor R (Biologics: Targets & Therapy)
Ranjit Ranbhor Pergament & Cepeda LLC, Florham Park, NJ, 07932, USACorrespondence: Ranjit Ranbhor, Pergament & Cepeda LLC, Florham Park, NJ, 07932, USA, Tel +1 973 967 0490, Email ranjitranbhor@gmail.comPurpose: This review examines recent advances in monoclonal antibody (mAb) manufacturing, focusing on process optimization, cost reduction strategies, and emerging technologies. The analysis addresses critical challenges in current manufacturing processes while evaluating innovative solutions to improve production efficiency and economic viability.Methods: We conducted a comprehensive analysis of recent literature on mAb manufacturing, examining traditional batch processing, continuous processing, and hybrid systems. The review evaluates cost optimization strategies, including media development and process integration, while assessing the impact of emerging technologies, such as machine learning and advanced analytics, on manufacturing efficiency.Results: Recent studies demonstrate that continuous processing can achieve up to 35% cost savings compared to traditional batch processing to meet an annual production demand of 100– 500 kg, though this gain diminishes at larger scales. Hybrid facilities show accelerated break-even points, reaching profitability 2– 2.5 years earlier than traditional facilities. Advanced media optimization strategies, incorporating novel tripeptide delivery methods, have demonstrated up to 35% improvement in mAb titers. Integration of machine learning and advanced analytics has significantly enhanced process control and optimization capabilities.Conclusion: The evolution of mAb manufacturing technologies offers promising pathways for improving production efficiency and reducing costs. Scale-dependent considerations remain crucial in selecting optimal manufacturing strategies, while emerging technologies present new opportunities for process optimization. Future developments in continuous processing, advanced analytics, and cell line engineering will be essential in meeting growing global demand while ensuring economic viability and accessibility of mAb therapeutics.Plain Language Summary: Though monoclonal antibodies (mAbs) have changed therapy for cancer and autoimmune illnesses, they struggle with accessibility because of manufacturing complexity and high cost.Our analysis shows: continuous processing provides up to 35% cost reductions for 100– 500kg annual production in comparison to batch techniques; hybrid facilities reach break-even 2– 5 years sooner than conventional setups; and innovative tripeptide delivery systems increase mAb titers by 35%.The combination of machine learning and sophisticated analytics is most encouraging since it allows real-time monitoring and parameter modification to enhance product uniformity and resource use.These developments could increase patient access by opening doors to more reasonably priced mAb therapies, and they could also enhance manufacturing economic conditions for manufacturers. Although scaling issues remain, the combination of process innovation and computer technologies points to a revolutionary future for mAb production.Keywords: biosimilar, biomanufacturing, process optimization, continuous processing, cost reduction, machine learning, advanced analytics